Intramuscular Perforator Dissection with the Hydrodissection Technique - Singhal, Dhruv; Momoh, Adeyiza O.; Colakoglu, Salih; Qureshi, Ali; Tobias, Adam M.; Lee, Bernard T. (Journal of Reconstructive Microsurgery, 2013)
Background Perforator flap breast reconstruction requires increased time for safe perforator dissection, especially the intramuscular course. We describe an adjunctive technique using hydrodissection to assist with the intramuscular perforator dissection.Methods Hydrodissection techniques were used for perforator dissection in 45 consecutive patients (64 flaps) undergoing deep inferior epigastric perforator (DIEP) flap breast reconstruction. These patients were compared with 39 patients (55 flaps) immediately prior to the use of this technique. The study time frame was between March 2008 and March 2010. Patient demographics, complications, and operative times were collected through an extensive chart review.Results There were no major differences in complications between groups; there were no flap losses encountered during this series, and fat necrosis rates were similar (9.4% with hydrodissection and 14.5% without, p = 0.41). Total operative time for bilateral reconstructions decreased by 59 minutes (p = 0.13) and 21 minutes (p = 0.57) for unilateral reconstructions with the utilization of hydrodissection, though this was not statistically significant.Conclusions The use of hydrodissection to assist with intramuscular perforator vessel dissection is safe to perform, as there was no increase in complications. The procedures utilizing hydrodissection were faster, and surgeons using this technique found it easier to visualize the perforators and dissect through the intramuscular course.
Keywords: perforator flaps; breast reconstruction; hydrodissection